From centrosymmetric to noncentrosymmetric: intriguing structure evolution in d10-transition metal iodate fluorides. Issue 73 (13th August 2020) - Cao, Liling; Luo, Min; Lin, Chensheng; Zhou, Yuqiao; Zhao, Dan; Yan, Tao; Ye, Ning
Abstract : The first d 10 -transition metal iodate fluoride, centrosymmetric ZnIO3 F, was successfully transformed into noncentrosymmetric CdIO3 F, resulting from the asymmetric nature of the [IO3 ] − groups by the substitution of Zn 2+ with Cd 2+ . Abstract : Two new d 10 -transition metal iodate fluorides, centrosymmetric ZnIO3 F and noncentrosymmetric CdIO3 F, were successfully synthesized by intriguing structure evolution. Both compounds have higher thermal stability and CdIO3 F has a large SHG response and wide band gap. Our study may afford a viable route to design materials with excellent NLO functions.